Stress Management in Improving Teachers’ Commitment to School - Ardiansyah Ardiansyah; Ahmad Syukri; Idarianti Idarianti (Journal of Social Work and Science Education, 2026)
This research aims to formulate a theory of stress management in enhancing teachers’ commitment to the school at SMA Negeri 12 Bungo. The background of the study is the low level of teachers’ commitment to the school, which is assumed to be influenced by high levels of stress. The objectives of this research are: (1) to analyze stress management, (2) to analyze school commitment, (3) to reveal how stress management can enhance teachers’ commitment to the school, (4) to identify factors influencing stress management in improving teachers’ commitment to the school, and (5) to formulate a stress management theory as an effort to strengthen teachers’ commitment to the school at SMA Negeri 12 Bungo. The research method used is phenomenology with a qualitative descriptive approach, aiming to explore teachers’ and staff’s subjective experiences in managing stress and their commitment to the school. Data were collected through in-depth interviews, observation, and document analysis to gain a deeper understanding of the interaction between stress management and school commitment. The results show that teachers’ stress management at SMA Negeri 12 Bungo still faces challenges related to workload, support, and recognition. Teachers’ commitment is generally good, especially affective commitment, but still requires reinforcement in terms of sustainability. Stress management significantly contributes to enhancing commitment through coping strategies, social support, and work–life balance. The study formulates a stress management theory based on psychological balance, institutional support, and spiritual values as a framework to strengthen teachers’ commitment.